Symposium: Critical Friendships, Poetic Relations: Weaving Inspirited Pathways Through the Academy - Latremouille, Jodi; Bartlett, Stephanie; Hanzel, Stacey; Tait, Lesley (Journal of the Canadian Association for Curriculum Studies, 2020)
In this symposium presentation, we explore how four women scholars are drawn to one another as a sustaining and life-giving practice in the hetero-patriarchal world of academia. Institutional attitudes, power, hierarchy and oppression (Betasamosake Simpson, 2014; Foucault, 2008; Kumashiro, 2002) hold both a visible and an invisible presence in the academy as individuals struggle with increasing workloads, institutional accountability and competition. We base our foundational understandings of these conditions in critical theory (Freire, 2000), and turn to ecology (Abram, 1996; Jardine, 2006; Macy & Brown, 2014) and Indigenous philosophies (Smith, 2012) for a response that is messy, heart-full, multivocal and rooted in good relations. We weave poetry and narrative writing to describe the well-worn pathways in the academy and to critically reflect on how we might step away from them to create fresh and renewed paths. Walking alongside each other in a courageous sisterhood, we see our criss-crossing footsteps, woven together like a braid, creating strength and new possibilities through relationships. We engage Indigenous and literary métissage (Donald, 2012; Hasebe-Ludt et al., 2009) as a form of life writing (Richardson & St. Pierre, 2005) and we will invite our audience into a dialogue that explores the deep influence of these relations on our well-being and success on our personal and academic journeys.